Upaya Meningkatkan Kesegaran Jasmani Melalui Pendekatan Bermain dalam Pembelajaran Pendidikan Jasmani bagi Siswa SMP Negeri 1 Bungku Timur Sulawesi Tengah - Djumrah Djumrah (Universitas Pendidikan Mandalika, 2020)
This study aims to determine the physical fitness of students who are taught through a learning model with a play approach. This study uses a classroom action research method. The subjects of this study were 26 students of Class IX SMP Negeri I Bungku Timur. The research instrument used tests and the data analysis technique used qualitative and quantitative descriptive analysis. The results of this study indicate that the learning model with a play approach has an impact on changes in motivation and levels of students' physical fitness. This is because they can learn while playing. With this activity, students' cognitive, affective and psychomotor abilities can develop optimally.